2004
DOI: 10.1158/1055-9965.1558.13.10
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Hormone Receptor–Defined Breast Cancer: A Systematic Review of the Literature

Abstract: Breast cancers classified by estrogen receptor (ER) and/or progesterone receptor (PR) expression have different clinical, pathologic, and molecular features. We examined existing evidence from the epidemiologic literature as to whether breast cancers stratified by hormone receptor status are also etiologically distinct diseases. Despite limited statistical power and nonstandardized receptor assays, in aggregate, the critically evaluated studies (n = 31) suggest that the etiology of hormone receptor–defined bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(44 citation statements)
references
References 70 publications
0
44
0
Order By: Relevance
“…Greater parity and earlier timing of offspring are associated with a lower risk of hormone receptor-positive breast cancer (13,15,24,25). Risk of ER/PR-positive breast cancer might be reduced by higher parity through several potential mechanisms, including changing profiles of circulating reproductive hormones and terminal differentiation of mammary epithelium, rendering the breast less susceptible to carcinogenic influences.…”
Section: Discussionmentioning
confidence: 99%
“…Greater parity and earlier timing of offspring are associated with a lower risk of hormone receptor-positive breast cancer (13,15,24,25). Risk of ER/PR-positive breast cancer might be reduced by higher parity through several potential mechanisms, including changing profiles of circulating reproductive hormones and terminal differentiation of mammary epithelium, rendering the breast less susceptible to carcinogenic influences.…”
Section: Discussionmentioning
confidence: 99%
“…Although several genetic factors have been identified in breast cancer, most cases are attributed to environmental factors. At least, it is widely accepted that among risk factors, prolonged exposure to high levels of estrogen plays an important role in the initiation and development of breast cancer [141]. Indeed, studies in experimental animal models and cultured human cells strongly suggest that estradiol (E2), its interconvertible metabolite estrone (E1), and their estrogen quinones exert carcinogenic effects on breast tissue through several mechanisms [142].…”
Section: Discussionmentioning
confidence: 99%
“…ER and PR are the most widely studied markers in breast cancer ( 28 ), and their expression levels are used as predictive markers of response to endocrine therapy ( 29 ). This study assessed the effects of postmenopausal on ER and PR expression in breast cancer and found that ER and PR expression were significantly associated with postmenopausal duration.…”
Section: Discussionmentioning
confidence: 99%